Hacking Mythology: Ancient Legends in Modern Packaging - lasaiba, Mohammad Amin (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2021)
This study discusses how ancient mythology is reinterpreted in various forms of modern media to reflect contemporary social and cultural issues, including literature, film, visual arts, and education. Through a literature review method, this research explores how legendary narratives, rooted in ancient traditions, remain relevant in addressing the challenges of the modern age. The review shows that mythological adaptations often explore essential themes such as gender justice, identity, and environmental sustainability. This study also highlights how technology and digital art have opened new avenues for interaction and reinterpretation of these myths, making them more dynamic and relevant to today's audiences. By incorporating various findings from recent academic sources, this study affirms that ancient mythology survives in modern culture and plays a significant role in shaping and reflecting collective identity and social discourse in the digital age.